TEENAGE MINDS: WHERE EGOCENTRISM MEETS CREATIVITY - Sohi, Kamalpreet Kaur; Janjhotra, Preeti (International Journal of Research -GRANTHAALAYAH, 2025)
This study examines the relationship between adolescent egocentrism and creative thinking, exploring whether heightened self-focused cognition predicts enhanced creative abilities. Drawing on Elkind’s (1967) theory of adolescent egocentrism namely the personal fable and imaginary audience. We investigate how these two constructs correlate with creative thinking, measured by the Torrance Tests of Creative Thinking (TTCT). A convenient sample of 350 adolescents (ages 16–18) completed assessments of egocentrism and creativity. Results revealed a significant positive association between personal fable ideation and creativity scores indicating that adolescents who have strong beliefs in their uniqueness come up with more novel ideas. Imaginary audience tendencies, however, did not significantly correlate with creativity. These results suggest that, through promoting nonconformity, some egocentric qualities may stimulate creative potential during adolescence. By elucidating the relationship between normative cognitive biases in adolescence and creative cognition, the study advances developmental psychology. These results offer actionable insights for fostering creative development in educational setting.